2020
DOI: 10.7555/jbr.34.20200013
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to environmental bisphenol A inhibits HTR-8/SVneo cell migration and invasion

Abstract: Environmental pollutants, such as bisphenol A (BPA) have recently been implicated in the development of adverse birth outcomes. However, the underlying teratogenic mechanisms remain unclear. We investigated the effects of BPA on the migration and invasion of human primary extravillous trophoblast HTR-8/SVneo cells. Our results indicated that BPA reduced cell migration and invasion. Moreover, it altered the ratio of matrix metalloproteinases (MMPs) and tissue inhibitors of MMPs (TIMPs) by downregulating MMP-2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Data were presented as the mean ± SD and processed using GraphPad Prism 8.0 (GraphPad Software, San Diego, USA). Data were in accordance with the normal distribution by Shapiro-Wilk test [ 27 ], and comparisons were conducted using one-way ANOVA [ 28 ] followed by Tukey’s post hoc test [ 29 ]. P < 0.05 was considered to indicate a statistically significant difference.…”
Section: Methodsmentioning
confidence: 99%
“…Data were presented as the mean ± SD and processed using GraphPad Prism 8.0 (GraphPad Software, San Diego, USA). Data were in accordance with the normal distribution by Shapiro-Wilk test [ 27 ], and comparisons were conducted using one-way ANOVA [ 28 ] followed by Tukey’s post hoc test [ 29 ]. P < 0.05 was considered to indicate a statistically significant difference.…”
Section: Methodsmentioning
confidence: 99%
“…In mouse placenta, BPA causes a decrease in the labyrinthine and spongiotrophoblast zone proportions with narrowing of the intervillous spaces [ 34 , 35 , 36 , 37 ]. The exact mechanisms as to how this occurs seems to be debatable; matrix metalloproteinase-2/9 (MMP2/MMP9) seems to be involved, but upregulation or downregulation occurs depending on the model used [ 34 , 35 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Few studies about the effect of BPA on the trophoblast migration were performed [67][68][69]74], while no information is available yet on the effect of BPS on this process. Present results indicate that only BPA affected cell migration ability.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to cell proliferation, also data on BPA effect on HTR8/SVneo cell migration are conflicting. Some studies [67,68,74] observed that migration and invasion were reduced following BPA exposure, while others [69] assessed that BPA enhances cell migration through ERK1/2 stimulation. The present work reports a reduction of migration at micromolar BPA concentrations.…”
Section: Discussionmentioning
confidence: 99%